Constraining in reimbursement criteria and the adherence to anti-osteoporosis medications (AOMs) in Taiwan: Urbanization makes the difference - Chen-Yu Wang; Tsung-Han Yang; Shau-Huai Fu; Jawl-Shan Hwang; Ho-Min Chen; Jou-Wei Lin; Chih-Cheng Hsu; Yin-Fan Chang; Chih-Hsing Wu; Ding-Cheng Chan; Rong-Sen Yang (Journal of the Formosan Medical Association, 2023)
Background: The Bureau of National Health Insurance in Taiwan implemented a new reimbursement scheme incorporating bone mineral density (BMD) criteria on Jan. 1, 2011. This study aimed to investigate a real-life 11-year secular trend of adherence in new AOMs users and evaluated the change of adherence to AOMs therapy in different urbanization areas after reimbursement criteria were restrained. Methods: We used Taiwan's National Health Insurance Research Database to identify new AOMs users as our study population. The AOMs in this study included denosumab, zoledronate, ibandronate, alendronate, raloxifene, and risedronate. The first prescription date of AOMs was defined as the cohort entry date. The adherence rates within one year after initiation were assessed. Results: High adherence (≥75%) in the first year increased markedly after the new reimbursement scheme in 2011, changing from 31.8% in 2008, and 41.7% in 2011 to 54.2% in 2018. On the other hand, low adherence (<25%) decreased from 38.8% in 2008 to 14.6% in 2018. In addition, the switchers increased from 5.9% in 2008 to 9.3% in 2018, indicating a more flexible choice of AOMs. The proportion of high adherence to AOMs was highest in high-urbanization areas, and the proportion increased about two times from 30% in 2008 to 60% in 2018. Conclusion: The implementation of new reimbursement criteria in 2011 was associated with increased adherence to AOMs and the increase was most apparent in high-urbanization areas.